2012
DOI: 10.1111/j.1365-2249.2012.04661.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the interaction between astrocytes and encephalitogenic lymphocytes during the development of experimental autoimmune encephalitomyelitis (EAE) in mice

Abstract: SummaryThe nature of pathogenic mechanisms associated with the development of multiple sclerosis (MS) have long been debated. However, limited research was conducted to define the interplay between infiltrating lymphocytes and resident cells of the central nervous system (CNS). Data presented in this report describe a novel role for astrocyte-mediated alterations to myelin oligodendrocyte glycoprotein (MOG)35-55-specific lymphocyte responses, elicited during the development of experimental autoimmune encephali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 56 publications
1
20
0
Order By: Relevance
“…Astrocytes, as opposed to microglia and oligodendrocytes, express high levels of IFNGR1(2) in vivo and upregulate MHC-II expression upon stimulation with Interferon-γ in vitro (3), emphasizing their potential function as local antigen presenting cells in the CNS. In this context, early in vitro investigations demonstrated that expression of low levels of MHC-II on non-activated astrocytes results in a decrease of T cell proliferation (4) and induces hyporesponsiveness of T and B cells (5), potentially via secretion of the downmodulatory cytokine IL-27(6,7). In contrast, when activated with Interferon-γ, the ability of astrocytes to produce IL-27 is impaired resulting in increased proliferation and pathogenic potential of MOG-specific T cells ex vivo (6).…”
Section: Role Of Selected Pro- and Anti-inflammatory Cytokinesmentioning
confidence: 99%
“…Astrocytes, as opposed to microglia and oligodendrocytes, express high levels of IFNGR1(2) in vivo and upregulate MHC-II expression upon stimulation with Interferon-γ in vitro (3), emphasizing their potential function as local antigen presenting cells in the CNS. In this context, early in vitro investigations demonstrated that expression of low levels of MHC-II on non-activated astrocytes results in a decrease of T cell proliferation (4) and induces hyporesponsiveness of T and B cells (5), potentially via secretion of the downmodulatory cytokine IL-27(6,7). In contrast, when activated with Interferon-γ, the ability of astrocytes to produce IL-27 is impaired resulting in increased proliferation and pathogenic potential of MOG-specific T cells ex vivo (6).…”
Section: Role Of Selected Pro- and Anti-inflammatory Cytokinesmentioning
confidence: 99%
“…Moreover, Lymph node and splenic macrophages of IL-33-treated mice showed polarization toward an alternatively activated macrophage, which are anti-inflammatory. JF Yang et al (Yang et al, 2012a) found that in vitro astrocytes inhibited the proliferation and IFN-γ, IL-4, IL-17 and TGF-β secretion of MOG 35–55 -specific lymphocytes, an effect that could be ameliorated by IL-27 neutralization. However, when astrocytes were pretreated with IFN-γ, they could promote the proliferation and secretion levels of MOG 35–55 -specific lymphocytes.…”
Section: Interaction Between Astrocytes and T Cells Under Pathologmentioning
confidence: 99%
“…The interpretation is supported by a recent study showing that astrocytes inhibited proliferation and IFN- γ , interleukin- (IL-) 4, IL-17, and TGF- β secretion levels of encephalitic T cells in vitro unless they were pretreated with IFN- γ . They even promoted T-cell proliferation, presumably by additional antigen presentation [119]. The inhibitory effect of astrocytes could be ameliorated by IL-27 neutralisation [119].…”
Section: Interactions Of Astrocytes and T Lymphocytesmentioning
confidence: 99%
“…They even promoted T-cell proliferation, presumably by additional antigen presentation [119]. The inhibitory effect of astrocytes could be ameliorated by IL-27 neutralisation [119]. IL-27 has been shown to suppress Th17 cells and thereby EAE [120, 121].…”
Section: Interactions Of Astrocytes and T Lymphocytesmentioning
confidence: 99%
See 1 more Smart Citation